Wind tunnel testing on a generic model of a hybrid lifting hull - UlHaque, Anwar; Asrar, Waqar; Omar, Ashraf Ali; Sulaeman, Erwin (Instituto de Aeronáutica e Espaço, 2016)
In this research, an experimental investigation was carried out at the International Islamic University Malaysia - Low Speed Wind Tunnel facility on a generic model of a hybrid lifting hull. Based on the historical trends of non-rigid airships, the fineness ratio of the said hull has been selected equal to 4. Free stream velocity was kept at 20 m∙s–1 and, along with the estimation of aerodynamic parameters, longitudinal and lateral stability characteristics were determined over a range of angles of attack from −8° to +12° and angles of sideslip from −10° to +10°. Zero lift coefficient was obtained at −4.2°, and the corresponding value was found to be greater than that at zero angle of attack. The comparison of the experimental results with the existing analytical relationships of wing has revealed that such an airfoil shaped hull cannot be considered as a wing due to 37% less analytical value of lift coefficient than that obtained by CFD simulations of the said hull. Existing equation of form factor of hull for conventional airships was also revisited, and a correction factor equal to 1.16 in the fundamental drag equation of aircraft’s fuselage was also proposed for fineness ratio equal to 4. Trends of the experimental data and comparison of the same with the theoretical calculations and computational results posed some interesting findings. The longitudinal and directional stabilities of a hybrid lifting hull were found to be statically unstable